Computer Learning of Small Math Using MATΣ MATX in English Class - Mitrović, Petra (Array, 2008)
An increasing trend of computer use at primary school level has caused changes in the learning style, using dynamic hybrid model including multimedia learning through a play and as a supplement to the classical teaching approach. For this purpose, a simple web-based application has been created, called MATΣ MATX, for children (7 to 9 years) in their study of basic mathematical principles (numbers up to 20, mathematical operations of addition and subtraction) for four language skills in English teaching class. A study was carried out on two test groups, trying to determine the potential usefulness of such a computer programme in the everyday teaching environment. The results of the study are presented in this paper.